2019
DOI: 10.1038/s41598-019-52677-6
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and economic benefits of abandoning invasive surgical procedures and enhancing animal welfare in swine production

Abstract: Food-animal welfare is a major ethical and social concern. Pork is the most consumed meat worldwide, with over a billion pigs slaughtered annually. Most of these pigs routinely undergo painful surgical procedures (surgical castration, tail docking, teeth clipping), which farmers often reluctant to avoid, claiming it would increase cost and reduce production efficiency. Herein, this study indicates that these procedures compromise pigs’ health and condition. Replacing surgical castration with immunocastration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
0
13
0
2
Order By: Relevance
“…The wound is left to heal by secondary intention [ 1 , 4 , 5 , 6 ]. As an alternative to this procedure, there is growing interest in raising entire males, and/or the use of immunocastration by an anti-GnRH vaccine, which has shown to be effective in reducing boar taint and increasing growth performance in male pigs [ 7 , 8 ]. Whilst this review focusses on methods of assessing pain mitigation for surgical castration, the reader is referred to comprehensive review articles regarding surgical and non-surgical options and pig welfare [ 3 , 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The wound is left to heal by secondary intention [ 1 , 4 , 5 , 6 ]. As an alternative to this procedure, there is growing interest in raising entire males, and/or the use of immunocastration by an anti-GnRH vaccine, which has shown to be effective in reducing boar taint and increasing growth performance in male pigs [ 7 , 8 ]. Whilst this review focusses on methods of assessing pain mitigation for surgical castration, the reader is referred to comprehensive review articles regarding surgical and non-surgical options and pig welfare [ 3 , 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the current concern about animal welfare has emerged for customers, development of new method can replace castration practice is required (Morgan et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, rearing pigs in lower stocking density and with environmental enrichment may be a requirement to raise pigs with tails and testicles [ 19 , 20 , 84 ] and would have further positive impact on pigs’ welfare [ 85 ]. A recent study showed that replacing surgical castration with immunocastration, avoiding tail docking, teeth clipping, and providing environmental enrichment to pigs resulted in lower physiological stress and risks for injuries and death, and improved growth with positive economic returns—but not when these changes were made individually [ 86 ]. Thus, changing one specific practice while maintaining others may incur in costs for producers without real benefits for the animals, and fail to meaningfully contribute to the social acceptability of the production system.…”
Section: Discussionmentioning
confidence: 99%